PELAYANAN PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) OLEH PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) KOTA PEKANBARU. - Fuadi, Akmal; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the service of women victims of domestic violence by Pekanbaru P2TP2A and to know the inhibiting factors for the service of women victims of domestic violence by P2TP2A Pekanbaru City. This research was conducted at the Integrated Service Center for Empowering Women and Children (P2TP2A) in Pekanbaru City. This research is a type of qualitative descriptive research. The type of data used is primary data and secondary data, data obtained by observation, interviews and documentation studies with deliberately selected informants. The researcher determines the sample taken because there are certain considerations (purposive sampling). Informants in the study were Head of Division of Service and Health Division of Pekanbaru City P2TP2A, Counselor / Coordinator of Recovery and Health Services Division, Complaint Receiving Staff / Pekanbaru P2TP2A Secretariat, Clients / victims of domestic violence who reported to P2TP2A Pekanbaru City. The data analysis method used is data reduction, data model and withdrawal / verification conclusions. The results of this study indicate that the social service process in Pekanbaru City P2TP2A is the client reporting (coming directly, by telephone, or referral) then filling out the complaint form, the complaints receiving staff assessing and interviewing the client, then the client is referred to the service according to the client's needs and accompanied, staff receiving complaints and administrators monitor client cases and record and report. And the Pekanbaru P2TP2A inhibiting factor in overcoming the problem of domestic violence includes victims of domestic violence itself, victims' families, communication, perpetrators of domestic violence, facilities and infrastructure as well as network collaboration. The service process by P2TP2A Pekanbaru City for women victims of domestic violence based on observations of researchers in the field is not optimal because it is not in accordance with the SOP and the Act that applies in P2TP2A Pekanbaru City.Â Â Keywords : Service, Organization, Program, Domestic Violence.Â